Teaching English Through Edmodo Application to Improving The Vocabulary Mastery of The Second Years Students of English Department of Universitas Muhammadiyah Parepare - Muhammad Suriadi Bin Ahmad Surianto (La Parole : Journal of Language Teaching and Pedagogy, 2019)
This study aimed to investigate whether applied Edmodo application can improve vocabulary mastery or not. Based on the observation at second years students of English Department of Universitas Muhammadiyah Parepare there were students less knowledge vocabulary mastery. It caused most students did not exploited the technology like android to study English. Beside, some of students just focus on social media and playing game. Those become some considerations of the researcher to conduct this research when doing an observation at English Department of Universitas Muhammadiyah Parepare, since the students shows less knowledge, one of media to solved the problem this research to find out whether or not used Edmodo application can improve vocabulary mastery. This research used quasi experimental method, with two group pre-test and post-test design. The population was the second years students of English Department of Universitas Muhammadiyah Parepare. The sample were drawn by using Edmodo application as experimental class and E-mail as control class that consisted 42 students which were B class as experimental and A class as control class. The data were acquired by using vocabulary mastery test. The vocabulary mastery test was applied by pre-test and post-test. The data required from vocabulary test was analyzed by using t-test and percentage technique. The result of the data analyzed shows that Edmodo application can improve vocabulary mastery of the second years students of English Department of Universitas Muhammadiyah Parepare significantly. It was proved by the mean score of the pre-test was (66.19) and the post-test (89.77). It showed that used of Edmodo application can improve vocabulary Mastery of the second years students of English Department of Universitas Muhammadiyah Parepare significantly. After analyzing the data by the the t-test formula, the result of t-test value in post-test was (2.42) and t-table value was (2.02108). Those indicated that H1 was accepted and H0 was rejected. The students who were taught through Edmodo application were better than the students who were taught through E-mail.